Pengaruh Keaktifan Belajar Matematika Terhadap Hasil Belajar Siswa SD - Rezky, Raizal; Jais, Ernawati; Ugi, La Eru; Hara, Nurharfiani (Mandalika Mathematics and Educations Journal, 2021)
This study aims to determine the effect of active learning on student learning outcomes in mathematics at Waruruma Elementary School Class IV for the 2020/2021 academic year. This research is an Ex-post Facto research. The population in this study were all fourth grade students of Waruruma Elementary School which consisted of 2 classes with a all of 41 students. The sample used in this study was the entire population of 41 students. The instruments used are in the form of questionnaires and documentation, where the documentation is the students mid semester test. From the results of descriptive analysis of the data shows that the level of students learning activity in general is still in the medium category. Where as many as 19,51% of students are in the high category, as many as 65,85% of students are in the medium category and as many as 14,63% of students are in the low category. As for the level of students’ mathematics learning outcomes in the high category. Where as many as 51,22% of students are in the high category, as many as 34,15% of students are in the medium category and as many as 14,63% of students are in the low category. The results of the study concluded that it showed that learning activity had an effect on student learning outcomes in Mathematics for Class IV at Waruruma State Elementary School for the 2020/2021 academic year. This is indicated by a significant value of 0,00 < 0,05.